Effects of ferulic acid on muscle development and intestinal microbiota of zebrafish. Issue 2 (27th September 2021) - Yin, Xiaoyu; Liu, Wuyun; Chen, Hao; Qi, Chelimuge; Chen, Hongsong; Niu, Huaxin; Yang, Jingfeng; Kwok, Kevin W. H.; Dong, Wu
Abstract: Ferulic acid (FA) is one of a common ingredients in Chinese herbal medicine. FA has the interesting property of promoting growth and improving meat quality in livestock, but the mechanism is not understood. This study evaluated both safety and mechanism of efficacy in zebrafish model. At 15 μg/mL or above, FA led to pericardial oedema and delayed growth in zebrafish embryos. Dietary FA promoted growth and feed assimilation in male adult zebrafish. Genes related to myogenic development ( myod1, myog and myf5 ) were significantly upregulated by FA and muscle fibre width in skeletal muscle was increased. At 20 µg/g, FA significantly increased number of goblet cells in zebrafish intestinal tissue, and gut microbiota composition also changed. Based on 16s rRNA gene sequences, 20 μg/g FA decreased Firmicutes and increased Bacteroides. 20 μg/g FA also stimulated the expression of PPAR ‐ α, a gene associated with fat metabolism, and decreased the expression of PPAR ‐ β and PPAR ‐ γ . These gene expression changes were beneficial to fatty acid synthesis and metabolism and decreased fat deposition. Our overall results indicated that FA can be a safe growth promotor in fish particularly in skeletal muscles.